HOG PRICE SHORT FORECASTING AS AID-FACTOR OF PRICE RISK MANAGEMENT IN AGRICULTURE - Lira, Jarosław; Śmiglak, Magdalena; Zielińska, Anna (Acta Scientiarum Polonorum. Oeconomia, 2006)
Within last 15 years the polish agriculture market is characterized by high price volatilities of agro-food raw materials and goods, which has been directly influencing returns of production cost. At each stage of the production chain, raw materials have been changing their properties and chain participants’ are exposed to price risk breeding their incomes’ uncertainty. Growing importance of liberalization process in the farming husbandry and less interventionism in CAP, have had a vital impact on price risk and its management. Due to the fact that risk in agricultural is unavoidable, furthermore, it’s a fundamental fact of enterprise life – knowledge about economic risk and managing price risk – will surely affect the process of income stabilization in agriculture. The aim of this article was to present the volatility of hog prices on the polish meat market from 01.01.1990 to 31.07.2006 and its forecast from 01.08.2006–30.06.2007 using Winters’ multiplicative forecasting model. According to underdone research on price volatility of chosen agro-food goods, especially on hog price volatility, it is to be pointed out that there are observed cyclic fl uctuations, so called: pig cycles, which have their own independent mechanism, different from the mechanism of condition-dependent cycles.